Specific internal and external attentional focus instructions have differential effects on rowing performance. (September 2020) - Neumann, David L.; Walsh, Nicholas; Moffitt, Robyn L.; Hannan, Thomas E.
Abstract: Directing an individual to focus their attention on internal or external cues can influence performance of skill-based and endurance sports. The present study examined the effects of switching attention across different types of internal and external attentional foci in a rowing task. Novice rowers (19 male, 47 female) focussed attention on one of four different internal cues (or one of four different external cues) at discrete time points while completing a row on an ergometer. Overall, a focus on internal cues resulted in longer distance, higher power output, and higher heart rate than a focus on external cues. However, for the internal condition a focus on arm and leg muscles was associated with higher performance than a focus on breathing. For the external condition, a focus on exerting force on the handle produced higher performance than a focus on the movements of the handle or seat or on the sounds of the ergometer. Global instructions to focus internally or externally influenced performance, but the specific effects within these broad categories were also variable. The advice given to athletes and recreational exercises should consider both the broad attentional focus direction and the specific cues of the task to which attention is directed. Highlights: Novice rowing performance can be influenced by different attentional foci. Internal focus of attention produced better rowing performance than external focus. For internal, a focus on the arms and legs was better than a focus on breathing. For external, a focus on the handle was better than a focus on movements or sounds. A focus on proximal cues elicits greater physical effort than distal cues.